2005
DOI: 10.1262/jrd.16008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of In Utero Exposure to Bisphenol A on mRNA Expression of Arylhydrocarbon and Retinoid Receptors in Murine Embryos

Abstract: Abstract.To evaluate the effects of bisphenol A (BPA), a candidate endocrine disruptor (ED), on embryonic development, we examined the mRNA expression levels of the arylhydrocarbon receptor (AhR), which binds with many EDs and plays crucial roles in xenobiotic metabolism, and of the retinoic acid receptor (RAR) α and retinoid X receptor (RXR) α, key factors in nuclear receptordependent retinoid signal transduction, in murine embryos exposed in utero to BPA (0.02, 2, 200, and 20,000 µg/kg/day) at 6.5-13.5 or 6.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 39 publications
(57 reference statements)
3
43
2
Order By: Relevance
“…Nishizawa et al (2005b), supported by the Japanese Ministry of Education, Culture, Sports, Science, and Technology and by the Japan Society for the Promotion of Science, examined the effects of bisphenol A exposure on expression of mRNA for arylhydrocarbon and retinoid receptors in mouse embryos. ICR mice were fed standard diet (CM; Oriental Yeast).…”
Section: [No Additional Information Was Provided For Statistical Analmentioning
confidence: 99%
See 2 more Smart Citations
“…Nishizawa et al (2005b), supported by the Japanese Ministry of Education, Culture, Sports, Science, and Technology and by the Japan Society for the Promotion of Science, examined the effects of bisphenol A exposure on expression of mRNA for arylhydrocarbon and retinoid receptors in mouse embryos. ICR mice were fed standard diet (CM; Oriental Yeast).…”
Section: [No Additional Information Was Provided For Statistical Analmentioning
confidence: 99%
“…Neural and Behavioral Endpoints Following Oral Administration: Several studies addressing effects on neural and behavioral endpoints have been conducted following gestational and lactational exposure [rats: (Funabashi et al, 2004a;Negishi et al, 2004a;Della Seta et al, 2005)]; mice: [(Palanza et al, 2002;Nishizawa et al, 2003Nishizawa et al, , 2005bLaviola et al, 2005;Ryan and Vandenbergh, 2006)], pubertal exposure [rat: (Akingbemi et al, 2004;Della Seta et al, 2006;Ceccarelli et al, 2007)], and exposure during adulthood [gerbils: (Razzoli et al, 2005)]. …”
Section: Experimental Animal Studies Considered Bymentioning
confidence: 99%
See 1 more Smart Citation
“…Although actual BPA lowest observed adverse effects level (LOAEL) established by the National Toxicology Program's report (US Environmental Protection Agency 1993) is 50 mg/kg per day, there are several reports indicating that perinatal exposure to BPA in doses below LOAEL affects reproductive parameters in adult animals, such as neuroendocrine axis development (Khurana et al 2000, Ramos et al 2003, mammary gland and prostate morphology (Ramos et al 2001, Durando et al 2006, estrous cyclicity patterns (Rubin et al 2001), and sexual behavior (Carr et al 2003, Kubo et al 2003, Negishi et al 2004, Porrini et al 2005, Fujimoto et al 2006. This apparent controversy could be explained by the fact that BPA shows an inverted-U-shaped dose-response curve (Nishizawa et al 2005, Wetherill et al 2005, Zsarnovszky et al 2005, where much of the effects observed with low-dose treatments are absent in traditional high-dose toxicological studies.…”
Section: Introductionmentioning
confidence: 99%
“…The antagonistic activities of environmental pollutions may induced antagonist activity to RXRs. BPA has been identified as a RXR disruptor, an extremely low concentration of BPA significantly increased RXR mRNA expression in the cerebra and cerebella of murine embryos [28]. Our previous work also has demonstrated that BPA exhibiting antagonistic activities to RXR␤ at micromolar concentrations in vitro [29].…”
Section: Introductionmentioning
confidence: 71%